Analysis of customer satisfaction on Maybank Islamic Services in Seberang Jaya / Rohani Hashim - Hashim, Rohani (2025)
The rapid growth of Islamic banking has intensified competition with conventional banking. To remain competitive, improving service and product quality has become a priority for customer satisfaction. Customer satisfaction reflects an institution’s ability to meet consumer needs and plays a key role in fostering customer loyalty and ensuring sustained growth. This study aims to analyze customer satisfaction with Maybank Islamic's services in Seberang Jaya. While previous research has focused on conventional or general Islamic banking, studies on customer satisfaction specific to Maybank Islamic are limited. This research addresses that gap by examining factors influencing satisfaction. The study employs a quantitative approach, using Krejcie and Morgan’s formula to determine the sample size from 150 customers at Maybank Islamic Seberang Jaya. A total of 108 customers participated through structured questionnaires. Respondents were aged between 20 and 60 years and were active customers at the Seberang Jaya branch. Data collected were analyzed using the Statistical Package for the Social Sciences (SPSS) software to ensure precise and reliable analysis. SPSS was used to perform descriptive statistics, reliability tests, and inferential analyses to interpret the data effectively. The findings show that location, staff professionalism, and convenience are key factors in customer satisfaction. A strategic location enhances accessibility, while professional staff build trust. Convenience in banking services, such as efficient transactions, also contributes significantly to satisfaction. The results suggest that Maybank Islamic should enhance these areas by improving location strategy, staff training, and service convenience to better meet customer needs.